Integrasi Permainan Engklek dalam Kehidupan Kampus untuk Mengenalkan Budaya Bangsa - Ayu Anggraeni Dyah Purbasari; Afif Amir Amrullah (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2024)
The influence of global development in the field of technology has caused some younger generations to forget local cultural activities such as behavior, language, and traditional games, which ultimately may lead to a loss of love for the nation and the country. Universitas Pembangunan Nasional Veteran Jakarta is an educational institution with the slogan "Campus for the Defense of the Nation," making it highly appropriate to have efforts to introduce and preserve culture within the campus community. One of these efforts is to introduce the traditional game of engklek on campus. This research involves community service activities focused on creating engklek game facilities on campus so that students can recognize and practice it